The value of literature - Nünning, Ansgar; Nünning, Vera (REAL, 2021)
In the wake of the ‘ethical turn,’ there have been intense debates about the ethical dimension of literary works and the ways in which they serve to represent and disseminate values and norms. Against the backdrop of the current legitimation crisis of the humanities in an increasingly digital age, the present volume puts the value of literature itself onto the agenda of literary studies. The articles in this volume explore the cognitive, ethical, and cultural value of literature, demonstrating why literature matters and why it is worthwhile to read literary texts. The collection shows that literary fictions serve as important ways of meaning-, sense- and world-making, and that they are powerful laboratories for revalorising our hierarchies of values and for fostering cultural resources of resilience.
Keywords: Konferenzschrift -- 06.2019 -- Gießen; Literarische Wertung; Literatur; Englisch